Pengaruh Metode STEM Terintegrasi pada Materi Elektronika terhadap Kemampuan Analisis dan Pemecahan Masalah Siswa SMK - Pribadi, Pandu; Nurahman, Arip; Jufriansah, Adi (Universitas Nusantara PGRI Kediri, 2024)
This study evaluates the effect of the integrated STEM method in learning electronics material on the analytical and problem-solving abilities of vocational high school students. The method used is Classroom Action Research (CAR) involving class XI students of Industrial Electronics Engineering at SMK Negeri 2 Banjar. This study involved three cycles of action including planning, action, observation, and reflection. The results showed a significant increase in students' analytical and problem-solving abilities, indicated by an increase in the average score from 60.0 in the pre-test to 80.0 in the post-test in the third cycle. Observations also showed an increase in student participation, with 95% of students actively involved in learning in the last cycle. These results indicate the effectiveness of the STEM method in improving students' competence in the field of electronics as well as their readiness to face the challenges of the world of work or further education.